Essays on Kansas farmers’ willingness to adopt alternative energy crops and conservation practices - Fewell, Jason Edward (Kansas State University, 2013)
The adoption of new technologies on-farm is affected by socio-economic, risk management behavior, and market factors. The adoption of cellulosic biofuel feedstock enterprises and conservation practices plays an important role in the future of Kansas agriculture. No set markets currently exist for bioenergy feedstocks and farmers may be reluctant to produce the feedstocks without contracts to mitigate uncertainty and risk. Adoption of conservation practices to improve soil productivity and health may be affected by risk considerations also. The purpose of this dissertation is to study how market mechanisms and risk influence Kansas farmers’ willingness to adopt cellulosic biofuel feedstock enterprises and conservation practices on-farm. The first essay examines farmers’ willingness to grow switchgrass under contract using a stated choice approach. Data were collected using an enumerated survey of Kansas farmers and analyzed using latent class logistic regression models. Farmers whose primary enterprise is livestock are less inclined to grow switchgrass. In addition, shorter contracts, greater harvest flexibility, crop insurance, and cost-share assistance increase the likelihood farmers will grow switchgrass. The second essay examines how farmers’ risk perceptions impact conservation practice adoption. Factor analysis of survey data was used to identify primary risk management behaviors of Kansas farmers. A multinomial logit model of conservation practice adoption incorporating these risk behaviors was developed. Estimation results indicate that different risk management factors may have no significant impact on practice adoption. Farmers may not consider certain aspects of risk significant in their adoption decision. The third essay examines the effect of different risk management behaviors on farmers’ willingness to produce alternative cellulosic bioenergy feedstocks under contract. Data were collected using a farmer survey with a set of stated choice experiments and analyzed using factor analysis and latent class logistic regression models. While farmers approach risk management differently, the risk management behaviors identified have no significant impact on farmers’ willingness to produce corn stover and switchgrass but have a negative impact on farmers’ willingness to produce sweet sorghum as a biofuel feedstock. These results may indicate that farmers are indifferent toward adopting new bioenergy cropping enterprises when traditional crop production is profitable and more certain.
Keywords: Farmers; Cellulosic biofuel; Conservation; Stated choice; Latent class models; Risk; Economics, Agricultural (0503)